ASSESSING THE IMPACT OF BANK RISK FACTORS ON TURKISH BANK’S STOCK RETURNS USING THE EGARCH-M MODEL (Third Sector Social Economic Review, 2019)
This study examines the effects of interest rate, exchange rate and credit risk factors on Turkish banks’ stock returns using weekly bank-level data from 01 January 2002 to 4 April 2019. The first order autoregressive exponential GARCH in-mean (EGARCH-M) model is estimated for 10 Turkish commercial banks. The results indicate that: (i) different banks are prone to different type of risks and the magnitude of risk exposure coefficients differ across banks with different characteristics; (ii) credit risk, exchange rate and interest rate risk factors exert a negative and significant impact on stock returns of about six Turkish banks and bank portfolio; (iii) for 6 banks, increases in risk will not necessarily lead to an increase in the returns; (iv) current conditional variance (volatility) is a function of past surprises and past volatility and is changing by time for all banks; (v) the current volatility is more sensitive to old news than it is the news about recent surprises in the market; (vi) past innovations have significant asymmetric and leverage effect on current volatility for half of the banks in the sample; (vii) the positive and negative surprises have a symmetric effect on the volatility of bank returns; (viii) volatility of bank returns seems to have declined in post global financial crisis period compared to pre-crisis period.
Keywords: Foreign Exchange Risk; Interest Rate Risk; Credit Risk; Bank Returns; EGARCH-M